Macropods : the biology of kangaroos, wallabies, and rat-kangaroos - Coulson, G. M. (Graeme M.); Eldridge, Mark Derek Bruce (CSIRO Pub., 2010)
This book covers the proceedings of a major 2006 symposium on macropods that brought together the many recent advances in the biology of this diverse group of marsupials.